ANALYSIS OF ELECTRONIC MATERIAL USE OF BASIC MATERIALS, IN EMS STEEL EDM PROCESS 45 REVIEWED FROM THE ASPECTS OF ELECTRODES OF MASS REDUCTION AND SURFACE DAMAGE - Tiwan Tiwan (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2007)
The aim pf this research is to analyze characteristic of Cu-based material that has been used as electrode in EDM process. The research variables are wearness off electrode, weightloss and roughness of specimens of EMS 45 steel.Experimental methode was used in this research, which consists of preparation process and EDM test, EDM process, characterization and testingprocess. Analysis was done based on characterization and testing process. Testing process comprises electrode wearness, weightloss and roughness of the specimen.The result show that wearness of brass electrode is higher than bronze electrode. However, bronze electrode gives rapid weight loss. At current of 45 A and pulse on time 3 s, weight loss of EMS 45 steel was1,8 timefaster using bronze electrode, but wearness of brass electrode was 18,67 times faster. Surface roughness of EMS 45 steel was smoother using bronze electrode. Weight loss of EMS 45 steel and electrode wearness affected by current andpulse on time. Nevertheles, surface roughness of EMS 45 influenced by current, but not bypulse on time.